Reconstruction of Sharia Economic Procedural Law in Indonesia and Comparison of Sharia Economic Cases in Malaysia and Indonesia - Basir, Cik; Emirzon, Joni; Syaifuddin, Muhammad; Hasan, Sofyan (Nurani, 2024)
Sharia economy is a subsystem of the national economic system. As an economic system with distinctive Sharia principles, which is an integral part of the national economic system, it should have regulations that can provide appropriate legal certainty for the community. However, this study highlights several weaknesses related to the regulations governing the resolution of Sharia economic procedural law, including the limitations of Supreme Court Regulation (Perma) Number 14 of 2016 concerning Procedures for the Settlement of Sharia Economic Cases and the pluralistic nature of Sharia economic procedural law sources. The aim of this research is to analyze the weaknesses in the resolution of Sharia economic procedural law, leading to disparities in the pursuit of justice by individuals in Religious Courts. This normative problem demands a reconstruction of Sharia economic procedural law to align it with Sharia principles and the values embodied in Pancasila. Furthermore, this study will compare the Sharia economic procedural law in Malaysia, which adheres to the principle of persons professing the religion of Islam, in the resolution of Sharia economic cases. The legal research method used is normative juridical, thus this research analyzes based on three aspects: philosophical, juridical, and sociological, to identify the urgency of legal reform of Perma Number 14 of 2016 concerning Procedures for the Settlement of Sharia Economic Cases. The findings of this research recommend a judicial review of Perma Number 14 of 2016 to build a Sharia economic procedural law derived from Islamic law and capable of providing legal certainty in all aspects of Sharia economic cases.